2021
DOI: 10.1039/d1tb01696b
|View full text |Cite
|
Sign up to set email alerts
|

Structural effect of NIR-II absorbing charge transfer complexes and its application on cysteine-depletion mediated ferroptosis and phototherapy

Abstract: Second near-infrared (NIR-II) absorbing organic photothermal agents (PTAs) usually suffer from the laborious and time-consuming synthesis, therefore it is of importance to develop simple and easy-handle method to prepare NIR-II...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In addition, electron state can affect the bond length of the molecules; the degree of charge transfer can be evaluated by the change of bond length of acceptors. [16,56] The CTCs have the characteristics of adjustable properties and convenient preparation; electron delocalization, stacking mode, and energy band can be feasibly and controllably tuned by adjusting donors and acceptors, which provide opportunities for their specific applications. The CTCs have high photothermal conversion efficiency for photothermal imaging, photothermal therapy, and seawater desalination that are mentioned in other sections of this article.…”
Section: Ctcsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, electron state can affect the bond length of the molecules; the degree of charge transfer can be evaluated by the change of bond length of acceptors. [16,56] The CTCs have the characteristics of adjustable properties and convenient preparation; electron delocalization, stacking mode, and energy band can be feasibly and controllably tuned by adjusting donors and acceptors, which provide opportunities for their specific applications. The CTCs have high photothermal conversion efficiency for photothermal imaging, photothermal therapy, and seawater desalination that are mentioned in other sections of this article.…”
Section: Ctcsmentioning
confidence: 99%
“…In vivo experiments showed that the multifunctional F4TCNQ-based CTCs can effectively kill tumors under the combination of 1060 nm laser-triggered PTT and cell ferrotherapy. [16,56,101] Photothermal immunotherapy can effectively avoid the weakness of a single PTT and process a good inhibitory effect on distant tumors via immunotherapy, which has become a promising therapeutic strategy. F4TCNQ-based CTCs can combine with programmed cell death protein to suppress tumor immune evasion and improve NIR-II PTT.…”
Section: Anticancermentioning
confidence: 99%
See 1 more Smart Citation
“…Red and deep-red fluorescent materials have received tremendous scientific and commercial attention over the last few decades, owing to their applications in organic light-emitting diodes (OLEDs), biological imaging, night-vision devices and so forth. [1][2][3][4][5][6] Generally, constructing the donor-acceptor structure and extending p-conjugation are the most frequently applied approaches to achieve red fluorescent materials. 7,8 However, high-efficiency red light-emitting materials are still rare compared with green and blue emissive materials due to the resonance of the vibrational wave function of the excited state and the ground state, which may accelerate the non-radiative transitions and cause a low photoluminescence quantum yield (PLQY).…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Fortunately, our group has previously observed that the CTCs containing thiol-sensitive acceptors not only possessed absorption in the NIR-II region but also showed GSH depletion induced ferroptosis, which can enhance antitumor efficacy. 23,24 Considering the high H 2 O 2 and GSH levels in the tumor microenvironment, it is highly desired that the CTCs should simultaneously have Fenton reaction properties and GSH depletion ability so that they can effectively break redox homeostasis and promote cancer cell ferroptosis. It is well known that ferrocene derivatives have a high electron-donating ability, and display antitumor activity for catalyzing H 2 O 2 to generate highly reactive $OH, [25][26][27] which should be a good donor for constructing versatile CTCs.…”
Section: Introductionmentioning
confidence: 99%